Efektivitas Prone Plank Exercise dan Bicycle Crunch Exercise terhadap Pengurangan Lingkar Perut pada Remaja - Krisna Dwi Patrisia, Ni Kadek; Najizah F; Syurrahmi; Amanati S (Lembaga Pengembangan Kinerja Dosen, 2025)
Waist circumference is a method used to determine central obesity, which is a condition of excess fat accumulation in the abdominal area, resulting in abnormal waist circumference in women >80 cm and men >90 cm. This study aims to determine the difference in effectiveness between prone plank exercise and bicycle crunch exercise in reducing waist circumference in adolescents. The research method used a quasi-experimental pretest-posttest two-group design. The sample consisted of 24 participants, divided into Group I (prone plank exercise) and Group II (bicycle crunch exercise), with each group consisting of 12 participants. Both groups underwent exercise therapy for 4 weeks, with a frequency of 5 times per week, with an intensity of 30 seconds per set, repeated 3 times. The measurement tool used was a calibrated midline. The results showed that Group I (prone plank exercise) experienced a reduction in waist circumference of 5.75 cm, while Group II (bicycle crunch exercise) had a reduction of 7.91 cm, indicating that both exercise therapies have an effect on waist circumference reduction. The difference test between groups resulted in p>0.05 (p=0.747), meaning there is no significant difference between the two exercise types.